Dattilogrammatica. Il "typewriter poem" come paradigma dell'immagine "informazionale" sulla scorta di Paul Valéry, Leo Steinberg, Walter Benjamin, Max Bense - Marcello Sessa (Ocula)
This paper punctuates some stages of the so-called "informational" theory of the image, which resignifies iconicity as data retention. It would first go to the origin, hypostatizing the horizontal reverse of forms theorized by Paul Valéry, crystallized at the extreme modernist edge of Leo Steinberg's "flatbed picture plane". And then to the Walter Benjamin of the reproducible, edited, anti-auratic image; it would also pass through the technological aesthetics of Max Bense, which arose in conjunction with concrete poetry. The essay would trace this itinerary with the analysis of a specific example, the "typewriter poem", going beyond the usual concretist lesson. It would finally demonstrate, with three case studies, how much the linguistic-typographical display alone can be a "tabula", on which a variety of functions of representation can act, in the form of data: graphic-pictorial (Eugen Gomringer), plastic (Carl Andre and Minimalism), sonic (Giovanni Fontana).